Evaluation of Sahiwal sires using part lactation records for increasing the milk production - RAJA, T V; GANDHI, R S (The Indian Journal of Animal Sciences, 2014)
Data on 586 daughters of 50 Sahiwal sires maintained at the Institute, over a period of 47 years (1961–2007) were used for the present study. The Sahiwal sires were evaluated on the basis of the breeding values for 3 traits, viz. FL305DMY, individual third month milk yield and cumulative 90 days milk yield using derivative free restricted maximum likelihood method and the relationship between the expected breeding values were estimated using the rank correlation. The heritability estimates of FL305DMY and individual third month milk yields were highly significant. The genetic and phenotypic correlations between FL305DMY and part lactation yields were highly significant. The study on the relationship of estimated breeding values among the 3 different traits, viz. first lactation 305-day or less milk yield, individual third month milk yield and cumulative 90 days milk yield revealed a higher degree of rank correlations. The per cent of common sires among the FL305DMY and individual third month yield was 60 and for FL305DMY and cumulative 90 days milk yield the corresponding per cent was 70 revealing that the selection based on any of the 3 traits exhibited a higher degree of similarity (>60%) in the ranking of top 10 Sahiwal sires. It was concluded that the Sahiwal sires may be evaluated on the basis of individual third month and/ cumulative 90 days milk yield for selecting the sires for increasing the FL305DMY using the DFREML method.